Pengaruh Penggunaan Teknik Wawancara Terhadap Kemampuan Menulis Karangan Argumentasi Siswa SMP Negeri 3 Karawang - Kuning, Layung; Setiawati, Siti; Ramdhania, Khairunnisa Fadhilla (Universitas Indraprasta PGRI, 2024)
This research aims to determine how much influence the interview technique has on the ability to write argumentation essays for grade 2 students of SMP Negeri 3 Karawang The research method used is an experimental method with control design.The sample was randomly taken from the affordable population of second grade students of SMP Negeri 3 Karawang for the 2022/2023 school year. The analytical techniques used in this study are normality test, homogeneity test and hypothesis testing with t-test at significance level a 0.05. Scores on experimental class scores reached 63 for the lowest grade and 90 for the highest grade with an average score of 78.43. Meanwhile, in the control class, 47 for the lowest value, 79 for the highest value and 62.63 for the average value After analysis for the normality test, the results of the control class calculated L of 0.0996 and in the experimental class of 0.148 smaller than the table L with n = 30, that is, 0.161. The results of the study with the t-test showed t count of 3.78 and t table with n-30 and significance level a = 0.05 obtained a price of 2.04 because t count is greater than t table (3.78 > 2.04), then Ho was rejected. Thismeans that the interview technique in this study affects the ability to write argumentation essays for students of SMP Negeri 3 Karawang.